Management Options for Obesity After Bariatric Surgery. Issue 1 (February 2015) - Buttelmann, Kristen; Linn, John G.; Denham, Woody; Ruiz, Melissa; Yetasook, Amy; Ujiki, Michael
<x xml:space="preserve">Abstract</x> Introduction: Many patients do not maintain weight loss after gastric bypass. We compared outcomes for patients undergoing diet/exercise intervention with patients undergoing surgical intervention through restorative obesity surgery—endolumenal, band over bypass, and endoscopic gastro gastric fistula closure. Methods: We hypothesized surgery would result in greater weight loss. A retrospective analysis was performed on a bariatric database. Patients who underwent gastric bypass and failed to lose weight were selected and evaluated after intervention. Records were reevaluated at 3, 6, and 12 months after intervention for primary outcomes, that is, weight loss and comorbidity resolution. Results: A total of 60 patients met the criteria. Forty-three underwent nonsurgical management; 17 underwent operative intervention. Mean body mass index decreased significantly in surgical patients compared with patients with supervised weight loss (P=0.001). Interventional patients trended toward better comorbidity resolution. Conclusions: Restorative obesity surgery—endolumenal, band over bypass, and endoscopic fistula closure results in greater weight loss and trend toward greater comorbidity resolution compared with diet and exercise.